2022
DOI: 10.1186/s12933-022-01584-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolocumab on top of empagliflozin improves endothelial function of individuals with diabetes: randomized active-controlled trial

Abstract: Background Sodium-glucose cotransporter 2 inhibitors (SGLT2i) improve endothelial dysfunction and reduce cardiovascular events in individuals with type 2 diabetes (T2D). Proprotein convertase subtilisin/kexin 9 (PCSK9i) inhibitors reduce cardiovascular events in high-risk patients. Whether the addition of PCSK9i to SGLT2i treatment adds benefits is not known. Objectives To assess the PCSK9-i effect on the endothelial function of T2D individuals und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…41,49,50 An RCT has shown that the short-term addition of evolocumab to empagliflozin in individuals with T2DM improves endothelial function, suggesting an additional role for the combination of the two agents in reducing cardiovascular risk. 51 The present study revealed that PCSK9 inhibitors alone increase the risk of SIDD and MOD, and it also demonstrated that statins alone increase the risk of SIRD. However, the effects of combining the two drugs on diabetes risk need to be further explored and monitored more carefully.…”
Section: Exposuresupporting
confidence: 66%
See 1 more Smart Citation
“…41,49,50 An RCT has shown that the short-term addition of evolocumab to empagliflozin in individuals with T2DM improves endothelial function, suggesting an additional role for the combination of the two agents in reducing cardiovascular risk. 51 The present study revealed that PCSK9 inhibitors alone increase the risk of SIDD and MOD, and it also demonstrated that statins alone increase the risk of SIRD. However, the effects of combining the two drugs on diabetes risk need to be further explored and monitored more carefully.…”
Section: Exposuresupporting
confidence: 66%
“…Available data suggest that PCSK9 inhibitors reduce LDL‐C by up to 60% more when applied in a statin background and are associated with a clinically significant reduction in cardiovascular events 41,49,50 . An RCT has shown that the short‐term addition of evolocumab to empagliflozin in individuals with T2DM improves endothelial function, suggesting an additional role for the combination of the two agents in reducing cardiovascular risk 51 . The present study revealed that PCSK9 inhibitors alone increase the risk of SIDD and MOD, and it also demonstrated that statins alone increase the risk of SIRD.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Zainordin et al [ 25 ] showed that 12 weeks of dapagliflozin add-on therapy to metformin and insulin did not alter FMD, and that there was no significant difference in FMD between the control and dapagliflozin groups. Sposito et al [ 26 ] showed that 16-week treatment with empagliflozin did not alter FMD. The EMBLEM trial, a multicenter, randomized, placebo-controlled, double-blind trial, showed that empagliflozin administered for 24 weeks did not alter the reactive hyperemia peripheral arterial tonometry index as an indication of endothelial function in patients with type 2 diabetes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2i are known for impairing endothelial dysfunction. Adding a PCSK9 inhibitor to SGLT2i treatment improved endothelial function assessed by FMD and the plasma concentrations of nitrate, nitrite, and isoprostane [ 64 ]. PCSK9 drugs suppress endothelial cell proinflammatory activation and reduce apoptosis in endothelial cells, smooth muscle cells, and macrophages [ 65 ].…”
Section: Endothelial Dysfunction Markers and Pcsk9 Inhibitorsmentioning
confidence: 99%
“…Treatment with a PCSK9 inhibitor given to type 2 diabetes (T2D) patients (110 individuals) along with SGLT2i treatment improved FMD and the bioavailability of NO. Increased NO may contribute towards improving endothelial dysfunction [ 64 ].…”
Section: Endothelial Dysfunction Markers and Pcsk9 Inhibitorsmentioning
confidence: 99%